If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(b+3)=4b-6
We move all terms to the left:
2(b+3)-(4b-6)=0
We multiply parentheses
2b-(4b-6)+6=0
We get rid of parentheses
2b-4b+6+6=0
We add all the numbers together, and all the variables
-2b+12=0
We move all terms containing b to the left, all other terms to the right
-2b=-12
b=-12/-2
b=+6
| 18+16f=-13 | | -5p-12=19 | | x*0.88=5191 | | 14-(x+9)=7x- | | 3t(t+2)-3t^2t=19 | | F=-4+6g | | (8x^2)-53-21=0 | | Y=12+(2.5x) | | 2(3^2x/7)=30 | | 7.1-(-(-2.5))=n | | 15=1+7(x-19) | | 16x-(5x-2)=90 | | 30x^2+40x=x | | (2x-1)/(3x-2)=0 | | -6+4m+10=15-2m | | 2x+26+2=x+18 | | 5(2x-3)=9+10x | | 7/6x=420x=360 | | 12+11x-1=22x | | 4v+v+10=4v-v | | r^2+9r+11=3 | | 2x-6+2x-3=19 | | 25n=700 | | x5=13 | | -3/4(m-8)=-2 | | x=9x+56 | | 8^5y=3 | | 10+20x=90 | | -5x-6=22+2x | | Y=3x+43 | | -2+2x=4-4x | | 3g−9+11g−21= |